Investigation of the Effects of Home-Based Exercise and Cognitive Training on Cognitive and Physical Functions in Cardiac Patients: The COVEPICARDIO Study Protocol of a Randomized Clinical Trial - Besnier, Florent; Dupuy, Emma Gabrielle; Gagnon, Christine; Vincent, Thomas; Grégoire, Catherine-Alexandra; Blanchette, Caroll-Ann; Saillant, Kathia; Bouabdallaoui, Nadia; Grau, Josep Iglésies; Bérubé, Béatrice; Olmand, Miloudza; Marin, Marie-France; et al. (Frontiers in Cardiovascular Medicine, 2021)
Introduction: During the COVID-19 pandemic, confinement measures are likely to produce collateral damage to health (stress, confusion, anxiety), especially in frail individuals and those living with cardiovascular disease (CVD). In cardiac patients in particular, these measures dramatically increase the level of physical inactivity and sedentary lifestyle, which can decrease cardiorespiratory capacity and increase the risk of acute events, rehospitalization, and depressive syndromes. Maintaining a minimum level of physical activity and cognitive stimulation during the COVID-19 crisis is essential for cardiac patients. This study is designed to document the effects of 6 months of home-based physical exercise alone or combined with cognitive training on cognitive and physical functions in patients with CVD over 50 years old. Methods and Analysis: 122 patients (>50 years old) with stable CVD and no contraindication to perform physical exercise training will be recruited and randomly assigned to one of the 2 following arms: (1) Home-based physical exercise alone, (2) Home-based physical exercise combined with cognitive training. The intervention lasts 6 months, with remote assessments performed prior to, mid and post-training. A follow-up 6 months after the end of the intervention (12 month) is also proposed. The primary outcome is cognition, including general functioning (Montreal Cognitive Assessment (MoCA) score), as well as performances on measures of executive functions, processing speed, and episodic memory. The secondary outcome is physical performance, including balance, gait and mobility, leg muscle strength and estimated cardiorespiratory fitness. Tertiary outcomes include mood, anxiety, and health-related quality of life as assessed by self-reported online questionnaires. Discussion: With the COVID-19 crisis, there is a critical need for remote exercise and cognitive training, and to further investigate this topic, in particular for cardiac patients. The present context can be viewed as an opportunity to perform a major shift from center-based programs to home-based physical exercise. This is especially important to reach out to older adults living in remote areas, where access to such interventions is limited. ClinicalTrials.gov: [https://clinicaltrials.gov/ct2/show/NCT04661189], NCT04661189.